Hyperreality of Gacoan Noodles in the Foodstagramming Trend on Instagram Social Media - Robin, Patricia; Elisti Halimuci (HM Publisher, 2024)
This research reveals the significant role of Instagram social media in creating the hyperreality of Mie Gacoan through the foodstagramming phenomenon. With the significant growth of Instagram users, especially in Indonesia, this platform has become the main platform for foodies to capture and share their culinary experiences. The foodstagramming trend, especially related to Mie Gacoan, shows how food photos uploaded on social media can create certain hopes and expectations for the restaurant. In the era of hyperreality, food prioritizes appearance over taste, creating a false reality conveyed through information technology. With the influence of foodies as “creators of reality,” Instagram has become a powerful communication tool, changing the way society views and consumes food. This research highlights the complexity of the interaction between social media, hyperreality, and culinary trends developing in the digital era.